Optogenetic control of horizontally acquired genes prevent stuck fermentations in yeast - David Figueroa; Diego Ruiz; Nicolò Tellini; Matteo De Chiara; Eduardo I. Kessi-Pérez; Claudio Martínez; Gianni Liti; Amparo Querol; José M. Guillamón; Francisco Salinas (Microbiology Spectrum)
ABSTRACT Nitrogen limitations in the grape must be the main cause of stuck fermentations during the winemaking process. In Saccharomyces cerevisiae, a genetic segment known as region A, which harbors 12 protein-coding genes, was acquired horizontally from a phylogenetically distant yeast species. This region is mainly present in the genome of wine yeast strains, carrying genes that have been associated with nitrogen utilization. Despite the putative importance of region A in yeast fermentation, its contribution to the fermentative process is largely unknown. In this work, we used a wine yeast strain to evaluate the contribution of region A to the fermentation process. To do this, we first sequenced the genome of the wine yeast strain using long-read sequencing and determined that region A is present in a single copy. We then implemented an optogenetic system in this wine yeast strain to precisely regulate the expression of each gene, generating a collection of 12 strains that allow for light-activated gene expression. To evaluate the role of these genes during fermentation, we assayed this collection using microculture and fermentation experiments in synthetic must with varying amounts of nitrogen concentration. Our results show that changes in gene expression for genes within this region can impact growth parameters and fermentation rate. We additionally found that the expression of various genes in region A is necessary to complete the fermentation process and prevent stuck fermentations under low nitrogen conditions. Altogether, our optogenetics-based approach demonstrates the importance of region A in completing fermentation under nitrogen-limited conditions.IMPORTANCEStuck fermentations due to limited nitrogen availability in grape must represent one of the main problems in the winemaking industry. Nitrogen limitation in grape must reduces yeast biomass and fermentation rate, resulting in incomplete fermentations with high levels of residual sugar, undesired by-products, and microbiological instability. Here, we used an optogenetic approach to demonstrate that expression of genes within region A is necessary to complete fermentations under low nitrogen availability. Overall, our results suggest that region A is a genetic signature for adaptation to low nitrogen conditions.